Arbitrator Diversity: Can It Be Achieved? - Sarah Rudolph Cole (Washington University Law Review, 2021)
The 2018 lawsuit Jay-Z brought against the American Arbitration Association (AAA) because the list of twelve arbitrators AAA provided in a breach of contract dispute did not include a black arbitrator highlighted ongoing concerns about the lack of diversity in the arbitrator corps. Given arbitration’s already less formal structure, one method for enhancing its legitimacy among diverse disputants would be to ensure greater diversity among those empowered to make decisions. Increasing diversity of neutral rosters––and more importantly, of the arbitrators ultimately selected from those rosters––may improve the public’s perception of the fairness and impartiality of the arbitration process. Increasing arbitrator diversity will have other benefits as well, including enhancing equal protection, equal opportunity, and complete participation norms. This Article suggests approaches that arbitration providers and participants in the arbitral process might adopt to enhance diversity in arbitrator selection. In particular, this Article posits that, while party control over arbitrator selection is a hallmark of arbitration, unbridled party selection may play an integral role in reducing diversity in the arbitrators selected. Among other things, winnowing to a single arbitrator, which the parties often undertake with relatively little information, may lead parties to rely on heuristics that incorporate explicit or implicit biases. One way to combat such concerns may be to reduce—at least at the margins—the extent of party control over the selection process. More specifically, adjusting the selection process to include a limited appointment aspect, rather than the traditional strike and rank approach, may substantially promote diversity while still preserving a strong role for party participation in arbitrator selection. In addition to direct arbitrator appointment, this Article explores other approaches that might enhance diversity in the arbitrator corps, including creating permanent panels of arbitrators, publicizing information about individual arbitrators, and implementing arbitrator evaluation processes. The proposed approaches would retain a strong role for party autonomy in the selection process while also providing a greater likelihood for diversity in the outcome of that selection process, in turn enhancing public perceptions of the fairness of arbitration as a dispute resolution mechanism.
Keywords: Arbitration; Arbitrator diversity; Dispute resolution; American Arbitration Association; Arbitrator selection